Association of metabolic abnormalities and the risk of hepatic fibrosis - Jiaping Fu; Yun Yi; Lurao Li; Xiawen Shu; Ying Chang (npj Gut and Liver)
Abstract Metabolic dysfunction-associated fatty liver disease (MAFLD) is characterized by a range of metabolic abnormalities, and its impact on the U.S. population requires further understanding. This study aimed to investigate the influence of each component of these metabolic abnormalities on hepatic steatosis and fibrosis in non-diabetic individuals. We analyzed data from 1711 non-diabetic participants in the National Health and Nutrition Examination Survey (NHANES) 2017–2018, which included transient elastography records. Steatosis was defined as a controlled attenuation parameter (CAP) value above 285 dB/m, and significant fibrosis was defined as a liver stiffness measurement greater than 8.0 kPa. Our results revealed a strong correlation between body mass index and waist circumference, with waist circumference being a better predictor of liver disease progression. All seven metabolic abnormalities were associated with increased severity of steatosis, and hypertension (OR = 2.43, 95% CI 1.55–3.82), elevated C-reactive protein levels (OR = 2.26, 95% CI 1.53–3.47), and waist circumference (OR = 2.19, 95% CI 1.39–3.45) were linked to significant fibrosis. These findings suggest that metabolic risk factors are associated with an increased risk of steatosis in non-diabetic subjects, while hypertension, central obesity, and chronic inflammation are related to significant fibrosis and may lead to worse prognosis.